Current scenario, services, concerns, and restoration perspectives of ponds in India - Rajput, Sneh; Kumari, Arpna; Rajput, Vishnu D.; Mandzhieva, Saglara S.; Minkina, Tatiana; Arora, Saroj; Kaur, Rajinder (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Ponds are self-sustaining and self-regulating ecosystems that are a vital part of the hydrological cycle and play a variety of roles in the biosphere. Ponds are diverse, extremely dynamic, and highly productive as they offer various services like harbor biodiversity, tool for combating water scarcity, have roles in pollution mitigation and carbon sequestration. Ponds also offer sustainable solutions to support climate change amelioration and aquatic resource management. However, ponds are the most neglected aquatic ecosystems, despite their huge ecological functions. Thus, ponds are debasing at an alarming rate as a result of increased anthropogenic activities and anthropogenically driven changes in natural processes, wreaking havoc on ecological health and water quality. In this context, the major threats to ponds include the dumping of solid waste, increased urbanization, pollution, encroachment and climate change which have resulted in the deterioration of ponds over the years. Sustainable management and restoration of ponds are crucial as this ecosystem offers a wide array of ecological functions. As a result, this research aims to assess the current state of ponds in India in terms of monitoring, ecological services provided, and the various threats to which they are subjected. Further, the discussions on management and perspective restoration strategies of this substantial ecosystem are also included. Thereby, this study suggests better conservation strategies for restoration, reclamation, and sustainable utilization of ponds.